وثائق لجنتى حفظ الاثار المصریة والآثار العربیة فى الفترة من 1881 م / 1956 : دراسة ارشیفیة دبلوماتیة - د. نهال یوسف حمدى (المجلة الدولية لعلوم المكتبات والمعلومات)
The study covered the topic in three aspects as follows The historical aspect: the topic was presented with a historical introductionto the Egyptian antiquities through the ages, and the role that the twocommittees played, explaining the origins, administrative dependence,competencies and financial resources of each. The archive side: An accurate inventory of the documents under discussionwas dealt with from two archival units, the House of Ministers and Ministers,and Abdeen documents. The multi-level archival description was also appliedby specifying the level of the description, and preparing models for archivaldescription cards for each level. The diplomaticaspect: The modern diploma curriculum was applied to twomodels of the documents under study, from the documents of the House ofRepresentatives, the ministers, and the Abdin documents.This is in addition to two attachments: for samples of the publisheddocuments and photocopies of documents.